Analysis of the Role of Accounting and the Code of Ethics For the Public Accountant Profession - Sulaiman, Nur Islamiati; Trisnaningsih, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore accounting and its role, as well as to analyze the ethical code that accountants must uphold. It employs a case study of ethical violations by public accountants that occurred at PT. Sunprima Archipelago Financing (SNP Finance). The analysis revealed that PT. Sunprima Nusantara Financing allegedly engaged in criminal activities, including embezzlement and money laundering. Additionally, the public accountant who conducted the audit violated theand principlessof the public accountant code of ethics, specifically integrity, objectivity, competence and professional prudence, and confidentiality. As a result of these violations, both the public accountant and PT. Sunprima Nusantara Pembiayaan faced sanctions from the Financial Services Authority (OJK), which included a freeze on business operations and administrative penalties and fines imposed by the Minister of Finance.